Overview of Nosocomial Urinary Tract Infections - Sarah Kassab Shandaway Al-Zamali; Noori Taha Alkhafaji; Mohammed Ibrahim Anwer; Ranaa W. Younus (Novel Research in Microbiology Journal)
Nosocomial urinary tract infections (UTIs) are the most common healthcare-associated infections (HAIs), accounting for a significant burden on patient outcomes and healthcare resources. Most cases are linked to catheter use, prolonged hospitalization, and poor infection control practices. This review aims to provide a comprehensive overview of nosocomial UTIs, covering their epidemiology, classification, risk factors, causative pathogens, resistance mechanisms, diagnostic advancements, and prevention strategies. Gram (-) bacteria, especially Escherichia coli, Klebsiella pneumoniae, and Pseudomonas aeruginosa are the leading uropathogens, often exhibiting multidrug resistance through biofilm formation, efflux pumps, and β-lactamase production. Emerging diagnostic methods, including molecular techniques, biosensors, and AI-assisted microscopy, offer faster and more accurate pathogen detection. Preventive measures such as minimizing catheter use, adherence to aseptic protocols, staff education, and antimicrobial stewardship remain essential. To mitigate the clinical and economic impact of nosocomial UTIs, integrated strategies combining rapid diagnostics, targeted therapies, and robust infection control measures must be prioritized. Continued research and system-wide implementation of best practices are essential to reduce infection rates and combat antimicrobial resistance.